Exploring English Learners’ Experiences of Using Mobile Language Learning Applications - Nehe, Berita Mambarasi; Eka Nurul Mualimah; Weny Widyawati Bastaman; Ira Arini; Sri Purwantiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Mobile language learning applications provide the potential to transform the way language is learned and it has been used for various purposes including language learning improvement. This investigation will contribute to which applications can support and be appropriate for students in learning English and explore more students’ experiences in using them. This research aimed to explore English learners’ experience of using Mobile Language Learning Applications in an informal learning context. This research employed a descriptive qualitative design with 25 college students. They share their experiences of using Mobile Language Learning Applications to learn English outside the classroom. The instrument used was an interview. The finding of this research showed all the participants confirm that they use mobile language learning to support their learning in English outside the classroom well which involves easy access to the materials, flexible place and time, and sophisticated features of the applications make students explore more and more learning English on the applications and they feel enjoy and fun regulate their learning pattern whenever and where ever, they find progress in learning English after they explore the apps, and students feel free to self-learning with their mobile device. It can be concluded that using Mobile Language Learning Applications outside the classroom allows learners to practice all the areas of English and these applications really supported learners’ experience to learn English based on their needs and self-learning.